STRATEGI KOMITE SEKOLAH DALAM MENDUKUNG PENINGKATAN MUTU PENDIDIKAN DI SMAN 1 PUNDUH PEDADA - Khairudin Khairudin; Sunarto Sunarto; Ferdian Utama (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the role and strategies of school committees in improving educational quality at SMAN 1 Punduh Pedada. School committees hold a strategic position as key stakeholders in participatory and accountable educational management; however, their role is often still administrative rather than strategic. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation involving principals, teachers, committee members, and parents. The findings show that the school committee has performed its roles as an advisory, supporting, controlling, and mediating agency, but these roles have not been fully optimized. Committee involvement in decision-making remains limited and tends to occur only at the final stage. Supporting factors include institutional support and community participation, while inhibiting factors include limited human resource capacity, weak coordination and communication, and the absence of structured strategic planning. The strategies implemented are still adaptive and not yet systematic, although they reflect collaborative efforts with the school. Therefore, optimizing the role of school committees requires strengthening strategic planning, improving stakeholder capacity, and enhancing communication systems to support sustainable educational quality improvement